Perilaku Mustahiq Dalam Memanfaatkan Dana Zakat Perspektif Ekonomi Islam - Usman Zainuddin Urif; Tatiek Herwanti; Moh. Huzaini (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2018)
This study aims to determine the mustahiq (Beneficiaries) behavior of the poor and fakir (Very poor) in utilizing zakat funds received from the National Amil Zakat Agency (BAZDA/ BAZNAS) in East Lombok Province of West South East Island, and to examine whether zakat funds can change mustahiq (Beneficiaries) status to be muzakki (Donors). This research using qualitative approach with 7 informants. Data collection methods used are observation techniques, interviews and documentation. Determination of informant researcher use purposive sampling and snowball technique. The results of this study indicate that the behavior mustahiq in utilizing zakat funds categorized on two behaviors of consumptive behavior and productive behavior. Consumptive behavior is the use of zakat funds for consumption needs (consumables), whereas productive behavior is zakat funds used for consumer needs, also set aside for the needs of productive needs such as business capital, savings and other productive business, so that funds can grow and not consumable. Zakat funds used for productive activities can change the status of mustahiq (Beneficiaries) into muzakki (Donors).